Varying association of nutrient intakes with quality of life in patients receiving different modes of dialysis - Guo, Yadi; Luo, Dongling; Yin, Li; Su, Xiaoyan; Yuan, Zhimin; Huang, Hui; Chen, Jie (Frontiers in Cardiovascular Medicine, 2024)
Background Nutrients are crucial for dialysis patients, especially elderly patients. Nutrition-related complications in dialysis patients are often closely related to cardiovascular aging. However, we know little about the effect of different nutrients on the commonly used outcome predictor, health-related quality of life (HRQOL). Therefore, this study investigated the associations between different nutrients and HRQOL among dialysis patients. Methods A cross-sectional study was conducted on 123 dialysis adults at multiple dialysis centers. The Short Form-36 Health Survey (SF-36) assesses HRQOL. Modified quantitative subjective global assessment (MQSGA) evaluates nutritional status. A 3-day dietary record evaluated nutrient intakes. Results Among the 123 participants, 79 received hemodialysis (HD), and 44 were on peritoneal dialysis (PD). Patients with PD had a higher SF-36 score than HD (525 ± 136 vs. 375 ± 179, P < 0.001). A negative association between nutrition status and HRQOL was observed in HD (regression coefficient β = −17.4, P < 0.001) but not in PD (β = −12.3, P = 0.07). For HD patients, the nutrition status was negatively correlated with intakes of carbohydrates, fiber, selenium, copper, and Manganese (β = −0.02, P = 0.032; β = −0.3, P = 0.031; β = −0.1, P = 0.006; β = −2.3, P = 0.025; β = −1.3, P = 0.003, respectively). Their HRQOL was positively associated with calories, fat, niacin, and vitamin E (β = 2.19, P = 0.035; β = 2.4, P = 0.043; β = 8.5, P = 0.044; β = 6.9, P = 0.017, respectively). Conversely, for patients with PD, only vitamin B2 was found to be adversely correlated with their nutritional status (β = −5.2, P = 0.037), and increased intakes of vitamin A, vitamin C and fiber (β = 0.1, P = 0.031; β = 0.8, P = 0.028; β = 15.8, P = 0.045, respectively) were associated with a better HRQOL. Conclusions The nutritional intake of PD patients and HD patients affects their quality of life differently. Macronutrients significantly impact HRQOL in HD patients, while vitamins have a more substantial impact on PD patients.